Optimization classification, algorithms and tools for renewable energy: A review - Iqbal, M.; Azam, M.; Naeem, M.; Khwaja, A.S.; Anpalagan, A. (Renewable & sustainable energy reviews, 2014)
Renewable energy technologies׳ systems are major components of the strategy to reduce harmful emissions and deal with depleting energy resources. It is necessary to deploy renewable energy sources in the best possible way such that cost is minimized and generation is maximized. In this paper, we present a review of different optimization methods for deployment and operation of renewable energy sources based generating units. Unlike other existing reviews, we carry out a general review of this research area, without limiting ourselves to any particular issue or geographic location. We examine this area with respect to different types of renewable energy sources, different modes of operations, types of objective functions for optimization and different geographical areas from which research publication are emanating. We present a general resource allocation problem and specify different possibilities for input, output, objective function and constraints. In addition, we review different objectives used in defining the optimization problems. We also present different types of linear and non-linear optimization algorithms used in renewable energy sources. Finally, we review optimization techniques for applications with respect to different end users.